The Influence Of Conflict Management Strategies And Employee Engagement On Employee Performance At PT. PLN (Persero) Ampera Branch Palembang Indonesia - Fajar, Isnin; Aliya, Sabeli (Commercium : Journal of Business and Management, 2024)
This study aims to analyze the influence of Conflict Management Strategies and Employee Engagement on Employee Performance at PT. PLN (Persero) Ampera branch. The research employs a quantitative approach with a causal associative explanatory design and utilizes multiple linear regression analysis. A total of 113 employees were sampled in this study using the total sampling method. The analysis results indicate that Conflict Management Strategies have a positive and significant effect on Employee Performance. Employee Engagement also demonstrates a positive and significant effect on Employee Performance. Simultaneously, both Conflict Management Strategies and Employee Engagement contribute positively to Employee Performance.